(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Artificial intelligence (AI) performs a progressively imperative role in management sciences and operational research. Intelligence is generally described as having the cognitive capacity to absorb information and use it to unravel complex dilemmas. According to researchers, intelligent machines will soon overtake human competencies. Intelligent machines and software that can think, assimilate, accumulate information, interact, control, and discern objects are known as artificial intelligence